A comprehensive review on multi-colored emissive carbon dots as fluorescent probes for the detection of pharmaceutical drugs in water. Issue 43 (24th October 2022) - Rajendran, Sathish; UshaVipinachandran, Varsha; Badagoppam Haroon, Kabir Hussain; Ashokan, Indhumathi; Bhunia, Susanta Kumar
Abstract : This review article signifies current progress in the synthesis of tunable fluorescent carbon dots and their potential for the detection of a variety of pharmaceutical drugs with detailed mechanism. Abstract : Exposure to constituent hazardous chemicals in medical products has become a threat to environmental health across the globe. Excessive medication and the mishandling of pharmaceutical drugs can lead to the increased presence of chemicals in the aquatic environment, causing water pollution. Only a few nanomaterials exist for the detection of these chemicals and they are limited in use due to their adverse toxicity, instability, cost, and low aqueous solubility. In contrast, carbon dots (C-dots), a member of the family of carbon-based nanomaterials, have various beneficial properties including excellent biocompatibility, strong photoluminescence, low photobleaching, tunable fluorescence, and easy surface modification. Herein, we summarize recent advancements in various synthetic strategies for high-quality tunable fluorescent C-dots. The root of fluorescence has been briefly explained via the quantum confinement effect, surface defects, and molecular fluorescence. The surface functional moieties of C-dots have been investigated in depth to recognize the various types of pharmaceutical drugs that are used for the treatment of patients. The modulation of C-dot fluorescence in the course of their interactions with these drugs has been carefully explained. Different types of interaction mechanisms behind the C-dot fluorescence alteration have been discussed. Finally, the challenges and future perspectives of C-dots have been proposed for the vibrant field development of C-dot-based drug sensors.